Floating elbows in adults: epidemiology, clinical presentation, management and prognosis: Brazzaville Teaching Hospital experience - Marius, Monka; Olivier, Ohoya Etsaka Terence; Didace, Massamba Miabaou; Albert, Ngatse Oko; Armand, Moyikoua (International Journal of Research in Orthopaedics, 2020)
Background: The objective of this study was to describe the epidemiological, clinical presentation, management and prognosis of classic floating elbows at the Brazzaville University hospital. Methods: This is retrospective descriptive study conducted in the Trauma-Orthopedics Department at Brazzaville University Hospital between January 2013 and December 2018. Four patients meeting the inclusion criteria underwent surgery. Open fractures were classified according to the classification of Gustilo and Anderson. Anatomical evaluation was based on the quality of fracture reduction and bone healing. The functional results were assessed according to the Mayo Clinic score. Results: The functional results were assessed according to the Mayo Clinic score of the 4 patients in our study, there were 3 men and 1 woman. The average age was 31 (28 and 34). They were all victims of traffic accidents. Three floating elbows were closed and one open at the humeral level with paralysis of the radial nerve. The closed fractures were treated by screwed plates and the open fracture by external fixator. Bone healing was achieved in 3 patients and we observed 1 case of aseptic nonunion of the radius. According to the Mayo Clinic score, 2 patients had a very good functional result, 1 patient an average result and 1 patient a poor result. Conclusions: Classic floating elbows are rare and their prognosis remains unpredictable, especially when they involve musculo-cutaneous or neurovascular damages. Their treatment must be surgical in the adult to avoid a prolonged immobilization which may lead to stiffness of the elbow. A multidisciplinary approach should then be taken into consideration.